The Relationship Between Parental Guidance And Student Learning Discipline During Pandemic Covid-19 - Nia Yan Sisni; Setiawati Setiawati (Universitas Negeri Padang, 2022)
The background of this research is the low discipline of students during online learning during the COVID-19 pandemic at SMA Pertiwi 1 Padang. Allegedly caused by the lack of parental guidance for children when studying from home, this study aims to: 1) describe parental guidance; 2) describe student learning discipline; 3) see the relationship between parental guidance and student learning discipline during the covid 19 pandemic.This research is a quantitative correlational study. The population in this study were all students of SMA Pertiwi 1 Padang in class X and class XI, which amounted to 521 students and 78 students were used as research samples using stratified random sampling technique. The data collection technique used a questionnaire, the data obtained were analyzed using descriptive analysis and the product moment correlation formula.The results of this study indicate: 1) parental guidance is categorized as low dominant 2) student discipline is categorized as low; 3) there is a significant relationship between parental guidance and student learning discipline during the covid 19 pandemic at Pertiwi 1 Padang High School. The research suggestions are: 1) it is hoped that formal school educators will pay more attention to student learning activities while online 2) it is expected that parents can guide their children in studying at home so that children can obtain maximum learning outcomes; and 3) it is hoped that further researchers will find or examine other variables that affect learning discipline, especially when studying from home.Keywords: Parental Guidance, Tutoring